Is Economics a Good Major for Future Lawyers? Evidence from Earnings Data - John V. Winters (Institute for the Study of Labor (IZA), 2015)
The current study examines earnings differences for practicing lawyers by undergraduate major with a focus on economics majors. Some majors do much better than others. Economics majors tend to do very well in both median and mean earnings, and both without and with controlling for individual characteristics. Electrical engineering, accounting, finance, and some other majors also do relatively well. This information is useful for undergraduates planning to attend law school and considering what undergraduate major field to study. Economics appears to be a very good option.
Keywords: I20; I26; J24; J31; 330; college major; earnings; economics major; lawyers; attorneys